Purwarupa Alat Ukur Daya Listrik Berbasis Netduino Plus - Irma Nirmalasari; Agfianto Eko Putra; Bambang Nurcahyo Prastowo (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2015)
Along with the development of technology a lot of methods of current, voltage and power factor measurement are developed. In this research is developing innovative instrumentation systems that use electrical power measuring devices that can be accessed online so that information on the number of power consumption and the amount of the bill can be accessed through the website . This system was designed using the Netduino Plus, ACS712 5A as sensor for detecting current and also use voltage gauges module that is used to detect the voltage with using the principle of current rectifier with a voltage divider circuit . The mechanism of usage electricity accumulation which is calculated for every second. Prototypes of electric power measuring instrument is successfully made and it is known that the current sensor system has the percentage accuracy of 98.4 %, the voltage measuring module has a percentage accuracy of 96.6 % .